Research on the Application of UAV Tilt Photography Technology in Engineering Project. Issue 2 (April 2021) - Wu, Bei; Li, Bingnan; Li, Shanshan; Li, Hongjie; Zhou, Rui
Abstract: Based on the teaching building project, the three-dimensional model generated by the fusion of tilt photography data processing process and panoramic image is applied to compare the three-dimensional model in the construction network plan with the real three-dimensional model. By using the advantages of fast modeling of tilt photography, the 3D real scene under 360 degree panorama is combined with different construction stages, and the models of different stages are visualized to realize the real preview of the project, so as to improve the quality of project construction, solve the problems in the construction process, and ensure the smooth progress of construction.